NAIL: Nucleic Acid detection using Isotachophoresis and Loop-mediated isothermal amplification1. Issue 7 (7th April 2015) - Borysiak, Mark D.; Kimura, Kevin W.; Posner, Jonathan D.
<x xml:space="preserve">Abstract</x> The NAIL device integrates isotachophoresis and loop-mediated isothermal amplification (LAMP) with mobile phone detection to extract, amplify, and detect nucleic acids from complex matrices in less than one hour.